ANALISIS SISTEM INFORMASI PENGELOLAAN DATA ALUMNI BERBASIS CODEIGNITER PHP FRAMEWORK - Gani, Alcianno G. (Universitas Dirgantara Marsekal Suryadarma, 2018)
Data management of alumni who still use the printed document means that data management can not be done quickly and there are still frequent errors and difficult to update. This problem can be overcome with a method that is developing the programming system. One of them with software. With this information management system software is expected to help the data management of alumni. Furthermore, the information management system software is expected to produce the information needed effectively and efficiently when in making decisions in managing human resources coming from the alumni. In order to be able to establish fellow alumni relationships for the better. Keywords: alumni data, web application, codeigniter